Fuzzy logic graph approach to elucidate structure-photocatalytic activity of carbon-doped titanium dioxide - Omar, Syahira (2020)
The discovery of photocatalytic water splitting of titanium dioxide (TiO2) electrodes by Fujishima and Honda (1972) trigger the extensive study of the structure and the improvement in the performance of TiO2 as photocatalyst in synthetic chemistry and environmental applications. Despite all the advantages provided from TiO2 compared to other semiconductor photocatalysts, its two main concern issues, which are large band gap energy and high recombination rate of photogenerated electrons and holes pairs, restraint its usage in practical applications. Hence, doping TiO2 with non-metal such as carbon is a promising way to modify the properties of TiO2 for the enhancement the photocatalytic performance of TiO2. Although there are many reports about the improvement of TiO2’s photocatalytic activity, the relationship between the structural and physical properties with the photocatalytic activity of carbon-doped TiO2 is still not well evaluated. In this study, a new approach has been proposed to elucidate the structure-photocatalytic activity relationship to better understand the dominant properties that determine the photocatalytic activities of carbon-doped TiO2 which is focusing under UV light system only. Fuzzy Logic Graph with the combination of Fuzzy Inference System modelling has been used as a new approach in determining the dominant factor for the structure-photocatalytic activity relationship of carbon-doped TiO2. The logic of expertise and from repetition of promising data were used. Fuzzy Inference System contains three fundamental steps including fuzzification, rule evaluation and defuzzification. This study includes four main stages which were data collection, development of Fuzzy Logic Controller, construction of Fuzzy Inference System and assessment of the results by sensitivity analysis. Experimental data that was used in this study was collected from experimental results obtained by our research group. To unveil the structure and physical properties-activity relationship, the type of crystalline phases, surface area, crystallite size and electron-hole recombination were chosen as the factors to be analyzed. Fuzzy Logic Graph analysis shows that surface area is a dominant factor for photocatalytic activity of carbon-doped TiO2, it is followed by rate of electron-hole recombination, phase and crystallite size. To summarize, with the help of Fuzzy Logic Controller, the structure physical properties activity relationship of carbon-doped TiO2 can be evaluated to show which factors that were responsible for the photocatalytic activity of carbon-doped TiO2. Although we used the limited source of experimental data to elucidate the physicochemical-photocatalytic properties relationship of carbon-doped TiO2, the correlation was successfully described in detail using Fuzzy Logic Graph.